2018
DOI: 10.14303/imaging-medicine.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying lipoma: literature review and analysis of radiological imaging

Abstract: Multiple theories exist regarding the pathogenesis of ossifying lipoma, though Lipomas are benign tumors consisting primarily of mature adipocytes. Imaging is important in distinguishing benign ossifying lipoma from more aggressive tumors such as well-differentiated liposarcomas. Early diagnosis of ossifying lipoma and understanding of its benign etiology prevent unwarranted medical intervention such as biopsies and surgical resection, as well as decrease patient anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…These include multidirectional differentiation of multipotent mesenchymal cells and metaplasia of fibrous elements into bone tissue, secondary to the existing "classic" lipoma in response to various external factors such as mechanical stress, repeated trauma, or ischemia. Nevertheless, aside from these hypothesis, it has also been suggested that osteolipoma can arise due to the factors released by monocytes in the circulation that induce the transformation of fibroblasts into osteoblasts, or perhaps due to an inadequate nutritional supply in the center of a large lipoma [6,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include multidirectional differentiation of multipotent mesenchymal cells and metaplasia of fibrous elements into bone tissue, secondary to the existing "classic" lipoma in response to various external factors such as mechanical stress, repeated trauma, or ischemia. Nevertheless, aside from these hypothesis, it has also been suggested that osteolipoma can arise due to the factors released by monocytes in the circulation that induce the transformation of fibroblasts into osteoblasts, or perhaps due to an inadequate nutritional supply in the center of a large lipoma [6,11].…”
Section: Discussionmentioning
confidence: 99%
“…On fat-suppressed T2weighted images, the mass displays high-signal foci with uniform suppression of the contained fatty tissue. Overall, these radiological characteristics are important in distinguishing this tumor from more aggressive fat-containing lesions such as liposarcoma [11]. The role of FNAC in assessing intraoral lesions is still debatable and has variable outcomes [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Histological evaluation is the most useful tool to reach the definitive diagnosis of ossifying lipoma. Surgical excision is usually the treatment of this entity, 7 and its prognosis is the same as that of conventional lipomas. 6 In the case of our patient, multiple confusing factors existed that suggested as a first possibility another type of neoplastic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the poor knowledge of this benign lesion, it is advisable a long-term follow-up in these patients although the recurrence is very low; in an extensive literature review conducted by Rombado and Madewell 7 in 2018, relapses of this type of tumors have not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation